Effect of SiC nanoparticle content on the properties of Ni-W-SiC nanocomposite thin films deposited by pulse current electrodeposition - Liu, Tianxiang (2023)
In this study, pulse current electrodeposition (PC) was used to fabricate Ni-W-SiCthin films on mild steel plates, by utilizing a Watts-type Ni liquid that contained SiC nano-particles (NPs). The films deposited with 9 g/L SiC NP showed a smooth, finely granular, and remarkably homogeneous surface structure. All films showed SiC NPs equally distributed on the Ni-W-SiC-NPs surface regardless of the starting SiC NP content. The calculations revealed that the thicknesses of Ni-W-SiC-NPs films deposited at 9 and 12 g/L were ≈ 27.3 and ≈ 22.2 μm, respectively. Moreover, the crystallite sizes decreased as the SiC NPs’ level was changed up to 9 g/L. Film particles became smaller (≈66 nm) but enlarged to 85 nm when SiC NPs level was changed from 9 g/L to 12 g/L, respectively. The deposited layer demonstrated an increase in microhardness from 490.2 HV to 881.5 HV with the addition of SiC nanoparticles. However, the hardness values of the Ni-W-SiC-NPs films became lower as the SiC NPs levels were changed from 9 to 12 g/L. Additionally, films fabricated using 9 g/L of SiC NP level demonstrated a minimal corrosion current (equal to 1.536 ×10−6 μA/cm2). The corrosion resistance of the film deposited at 9 g/L was about 5.3 times that of the film obtained at 0 g/L, indicating an excellent corrosion resistance. The study can provide the corrosion protection for water or oil pipes, metal containers and agricultural machinery.